Concept of emergence of a new coronavirus infection - Valentina G. Dorofeychouck; Stella A. Sher (Union of pediatricians of Russia, 2021)
This report presents a brief review of literature and the authors' concept of the emergence of the novel coronavirus 19 infection. The purpose of the work is to show the significance of lysozyme deficiency in the pathogenesis of COVID-19 based on data from literature sources and the results of the authors' past studies. The relevance of the study is due to the planetary scale of the spread of coronavirus infection, the appearance of SARS-CoV-2 with new aggressive signs, the difficulties of their treatment and prevention. Anatomo-functional connection of protective mechanisms of lysozyme, mucopolysaccharides of histohaematic barriers with preservation of immune, biochemical and tissue homeostasis is established. The loss of lysozyme, which has genetically determined enzymatic specificity, contributes to the development of damaging processes of immune, biochemical and tissue nature with manifestation in all organs and systems of the body. Inclusion of exogenous lysozyme in basic therapy and prophylaxis COVID-19 is proposed.